Design and Build a Pharmacy Location Mapping Information System in Batam City - Fendi Hidayat; Dwi Ratna Fitriyani; Fifin Oktaviani; Yoga Fitriana (Politeknik Negeri Batam, 2022)
Geographic information systems have been widely applied in the health sector, including to determine the location of medical clinics, midwife clinics, and pharmacies. Currently, in Batam City, there is no mapping-based system that is used to find out the distribution of pharmacy locations, so it is very difficult for the public to get information on the location of pharmacies that are close to their location. Therefore, in this study, an information system for mapping the location of pharmacies in Batam City was made by adopting GIS technology. The study used a descriptive analysis approach and was developed using the waterfall method in software development and UML as a design tool. The system produced in this study is proven to be able to provide pharmacy location information and assist admins in managing pharmacy location data.